A single-phase brookite TiO2 nanoparticle bridge enhances the stability of perovskite solar cells. Issue 4 (17th February 2020) - Shahiduzzaman, Md.; Kulkarni, Ashish; Visal, Sem; Wang, LiangLe; Nakano, Masahiro; Karakawa, Makoto; Takahashi, Kohshin; Umezu, Shinjiro; Masuda, Atsushi; Iwamori, Satoru; Isomura, Masao; Miyasaka, Tsutomu; et al.
Abstract : The high potential of Brookite TiO2 nanoparticles (NPs) bridges between perovskite and TiO2 CL, resulted in improved stability of PSCs. Abstract : Titanium dioxide (TiO2 ) based planar perovskite solar cells (PSCs) suffer from poor long-term stability and show hysteretic behaviour in the device characteristic curve. In addition to the exceptional bulk properties of the perovskite, the performance and stability are also highly dependent on the conduction band energy, conductivity, and electronic trap states of the TiO2 compact layer (CL). In this work, single-phase brookite (BK) TiO2 nanoparticles (NPs), synthesized via a hydrothermal method using a water-soluble titanium complex, are incorporated as a bridge between the perovskite and TiO2 CL. This resulted in uniform large perovskite grain growth with enhanced crystallinity, significant reduction in trap/defect sites and interfacial recombination as revealed by scanning electron microscopy (SEM), photoluminescence (PL), and impedance spectroscopy results, respectively. The resulting PSCs show highly reproducible power conversion efficiencies (PCEs) up to ∼18.2% ( vs. ∼15%) with a stable performance of 18% under continuous light illumination (1 sun) at the maximum power point tracking (MPPT) in contrast to only TiO2 CL based planar devices. To the best of our knowledge, this is so far the best photo-stability data reported for brookite NP based PSCs. Based on our present study, at the end we provide further direction to enhance the stability of planar PSCs.